Prevalence of syphilis among female sex workers and their clients in Togo in 2011 - Wemboo Afiwa Halatoko; Dadja Essoya Landoh; Bayaki Saka; Koffi Akolly; Yao Layibo; Issifou Yaya; Dodji Gbetoglo; Abiba Kere Banla; Palokinam Pitché (BMC, 2017)
Abstract Background During the last ten years, a resurgence of syphilis has occurred in many countries worldwide, including Togo. Previous studies have shown a wide range of syphilis infection among the female sex workers (FSWs), from 1.5 to 42.1%. In Togo, Key populations, including FSWs, are rarely involved in the sentinel surveillance programs to determine the prevalence of HIV and syphilis. The aim of this study was to determine the prevalence of syphilis among female sex workers (FSWs) and their clients in Togo. Methods We conducted a cross-sectional study in December 2011 targeting FSWs and their clients in Togo. Among participant who consented, we collected blood samples for syphilis and HIV testing. Results In total, 1,836 participants (1,106 FSWs and 730 clients) were included in the survey. Their mean age was 28.6 ± 9 years. The prevalence of syphilis was 2.2% (2.2% among FSWs compare to 2.3% among their clients, p = 0.82). This prevalence was higher among FSWs over 30 years old compare to those less than 30 years old (Odd Ratio (OR) =5.03; 95% CI [1.95-13.49]). Single FSWs were three times less likely to have syphilis than those living in couple or married (OR = 3.11; CI 95% [1.16-8.83]). Brothel based or declared FSWs were 4 times more likely to be infected by syphilis than secret ones (OR = 3.89; CI 95% [1.60-9.54]). Out of the 1,836 participants of the survey, 165 (8.9%) were HIV positive. Having syphilis was associated with HIV infection (OR = 3.41; IC 95% [1.53-7.41]). Conclusion This study showed that: i) the prevalence of syphilis among FSWs and their clients was high; ii) syphilis was significantly associated with HIV infection. It is necessary to increase awareness campaigns and emphasize on condom use among this key population group.